2006
DOI: 10.1248/bpb.29.1418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Five Phytosterols from Aloe Vera Gel as Anti-diabetic Compounds

Abstract: Of the more than 360 Aloe species known, Aloe barbadensis MILLER (Aloe vera) is the most widely used. Aloe vera contain two major parts: firstly, leaves containing a high concentration of anthraquinone compounds that have been used throughout the centuries as a cathartic and for medicinal purges; and secondly, a clear gel that has been used as a food and to treat burns and other wounds. 1,2) Several chemical components of the Aloe gel are thought to be responsible for its wound healing and immunostimulatory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
2
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 25 publications
7
134
2
11
Order By: Relevance
“…Similar to findings of the present study, a significant reduction in blood glucose level was observed after administration of phytosterols such as lophenol, 24-methyl-lophenol, 24-ethyl-lophenol, cycloartanol and 24-methylene-cycloartanol in non insulin dependent diabetes by Tanaka et al (2006). Arora et al (2009) also reported a significant reduction in total cholesterol, total triglycerides, LDL, and VLDL levels after supplementation of Aloe vera.…”
Section: Resultssupporting
confidence: 89%
“…Similar to findings of the present study, a significant reduction in blood glucose level was observed after administration of phytosterols such as lophenol, 24-methyl-lophenol, 24-ethyl-lophenol, cycloartanol and 24-methylene-cycloartanol in non insulin dependent diabetes by Tanaka et al (2006). Arora et al (2009) also reported a significant reduction in total cholesterol, total triglycerides, LDL, and VLDL levels after supplementation of Aloe vera.…”
Section: Resultssupporting
confidence: 89%
“…1= Glucuronic acid; 2=Stachyose; 3= Galacturonic acid;4=Sucrose; 5=Maltose;6=Lactose ; 7=D-glucose ;8=Glucose; 9=Xylose; 10=Galactose; 11= Rhamnose; 12=Mannose; 13=Raffinose ;14=Arabinose;15=Fructose; ;16=Mannitol;17=Sorbitol;18=ribose. compounds, which can counter the high cost and poor availability of the current medicines for many rural populations in developing counties (Tanak et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Jia et al (82) reported that topical applications of Aloe vera mucilage led to enhanced healing of wounds in both desert rats and rabbits. In general, Aloe vera contains a range of phytochemicals such as pyrocatechol, saponin, acemannan, β-mannan, anthraquinone, Cglycosides, diethylhexylphth-alate, bradykininase, oleic acid, phytol, and magnesium lactate along with water-soluble polysaccharides like glucomannan (75,(83)(84)(85). In addition to these components, vitamins (vitamin E and C) and amino acids do exist and may well play important role in acceleration of wound healing (77,86).…”
Section: Woundsmentioning
confidence: 99%